2006
DOI: 10.1007/s10800-006-9215-y
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical characterization of perovskite-based SOFC cathodes

Abstract: The electrochemical performance of La 0.58 Sr 0.4 Co 0.2 Fe 0.8 O 3-d (L58SCF), La 0.78 Sr 0.2 Co 0.2 Fe 0.8 O 3-d (L78SCF) and composite La 0.65 Sr 0.3 MnO 3-d -8 mol% Y 2 O 3 stabilized ZrO 2 (LSM-YSZ, 50:50 wt%) cathode electrodes interfaced to a double-layer electrolyte made of Ce 0.8 Gd 0.2 O 2-d (CGO) and YSZ was studied in the temperature range 600-850°C using impedance spectroscopy and current-overpotential measurements. The experiments were carried out in a single chamber cell using a three electrode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 29 publications
4
44
0
1
Order By: Relevance
“…Researcher have explored LSM-YSZ (composite) and LSCF cathodes with YSZ-CGO electrolyte by current over potential measurements and impedance spectroscopy, and it is observed that LSM-YSZ has higher area specific polarization resistance (1.8 Ω-cm 2 ) as compared to LSCF (0.4 Ω-cm 2 ) at 850 °C [51]. A lot of efforts/concentrations are being given to increase the performance of electrode for low and intermediate temperature SOFCs [10,37,39,40,[42][43][44][45][46][47].…”
Section: Cathodementioning
confidence: 99%
See 1 more Smart Citation
“…Researcher have explored LSM-YSZ (composite) and LSCF cathodes with YSZ-CGO electrolyte by current over potential measurements and impedance spectroscopy, and it is observed that LSM-YSZ has higher area specific polarization resistance (1.8 Ω-cm 2 ) as compared to LSCF (0.4 Ω-cm 2 ) at 850 °C [51]. A lot of efforts/concentrations are being given to increase the performance of electrode for low and intermediate temperature SOFCs [10,37,39,40,[42][43][44][45][46][47].…”
Section: Cathodementioning
confidence: 99%
“…Researcher have explored LSM-YSZ (composite) and LSCF cathodes with YSZ-CGO electrolyte by current over potential measurements and impedance spectroscopy, and it is observed that LSM-YSZ has higher area specific polarization resistance (1.8 Ω-cm 2 ) as compared to LSCF (0.4 Ω-cm 2 ) at 850˝C [51]. The solid state reaction that takes place between YSZ electrolyte and MIEC materials during synthesis can be evaded by impregnation of the cathode material into porous electrolyte structure that need low sintering temperature [8,10,12,53].…”
Section: Cathodementioning
confidence: 99%
“…4a, the 1-layer LSCF cathodes exhibited area specific resistances (ASR) of 0.088, 0.186, 0.43, and 1.16 Ω·cm 2 at 800 o C, 750, 700, and 650 o C, respectively, similar to those reported in the literature. 15) In contrast, the cells with 3-layer LSCF electrodes of graded microstructure displayed much better performance (Fig. 4b).…”
Section: Resultsmentioning
confidence: 92%
“…6 are the area specific polarization resistances of LSCF cathodes (3-layer and 1-layer) fabricated by tape-casting in the present work, together with data reported in the literature for LSCF cathode deposited on GDC or YSZ electrolyte. Clearly, the 3-layer LSCF cathodes fabricated by tape-casting display lower interfacial resistance than the 1-layer cathodes fabricated by other methods, including screen printing, 15,16) spray pyrolysis 20) and brush painting. o C, the improvement in performance of the 3-layer graded cathode is more dramatic, approaching an order of magnitude at operating temperatures 650-800 o C. Interfacial resistances of the 1-layer LSCF cathode prepared by tape casting were also indicated in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Recently, spray drying of solutions has been used to synthesize some polycationic oxides investigated in view of applications as magnetoresistive materials [6], high temperature superconductors [5], thermoelectric materials [7], piezoelectric materials [8] and electrode materials for lithium-ion batteries [9][10][11] or solid-oxide fuel cells [12]. We have recently reported another, more restricted, application, which is the preparation of composites by spontaneous phase separation of the components during the heat treatment [13].…”
Section: Introductionmentioning
confidence: 99%